2016
DOI: 10.1039/c6dt01568a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural diversity of trivalent rare-earth metal diisopropylamide complexes

Abstract: A series of rare-earth metal diisopropylamide complexes has been obtained via salt metathesis employing LnCl3(THF)x and lithium (LDA) or sodium diisopropylamide (NDA) in n-hexane. Reactions with AM : Ln ratios ≥3 gave ate complexes (AM)Ln(NiPr2)4(THF)n (n = 1, 2; Ln = Sc, Y, La, Lu; AM = Li, Na) in good yields. For smaller rare-earth metal centres such as scandium and lutetium, a Li : Ln ratio = 2.5 accomplished ate-free tris(amido) complexes Ln(NiPr2)3(THF). The chloro-bridged dimeric derivatives [Ln(NiPr2)2(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 107 publications
0
22
0
2
Order By: Relevance
“…The Lu–centroid(COT big ) distances are 171.91(4) pm and therefore significantly shorter than those in the related sandwich complex [Lu(COT′′) 2 ] – [Lu–centroid(COT′′) 184.5 pm], which is again probably due to the lower coordinative saturation of the Lu atoms. The Lu–Cl distances [264.0(1)–266.9(1) pm] are in the same range as those in other binuclear Lu complexes, for example, [Lu 2 (µ‐Cl) 2 (CpSiMe 3 ) 4 ] [Lu–Cl 263.9(1) and 265.3(1) pm, Lu–Cl–Lu 98.33(3)°] and [Lu 2 (µ‐Cl) 2 (N i Pr 2 ) 4 (THF) 2 ] [Lu–Cl 264.3(2)–268.9(2) pm, Lu–Cl–Lu 101.7(1)°] . The Lu–Cl–Lu angles in 5 are comparatively small at 86.77(3)–87.10(3)°, which might be due to the unique Lu 2 Cl 3 cage architecture instead of the planar Lu 2 Cl 2 ring present in the reference compounds.…”
Section: Resultsmentioning
confidence: 70%
“…The Lu–centroid(COT big ) distances are 171.91(4) pm and therefore significantly shorter than those in the related sandwich complex [Lu(COT′′) 2 ] – [Lu–centroid(COT′′) 184.5 pm], which is again probably due to the lower coordinative saturation of the Lu atoms. The Lu–Cl distances [264.0(1)–266.9(1) pm] are in the same range as those in other binuclear Lu complexes, for example, [Lu 2 (µ‐Cl) 2 (CpSiMe 3 ) 4 ] [Lu–Cl 263.9(1) and 265.3(1) pm, Lu–Cl–Lu 98.33(3)°] and [Lu 2 (µ‐Cl) 2 (N i Pr 2 ) 4 (THF) 2 ] [Lu–Cl 264.3(2)–268.9(2) pm, Lu–Cl–Lu 101.7(1)°] . The Lu–Cl–Lu angles in 5 are comparatively small at 86.77(3)–87.10(3)°, which might be due to the unique Lu 2 Cl 3 cage architecture instead of the planar Lu 2 Cl 2 ring present in the reference compounds.…”
Section: Resultsmentioning
confidence: 70%
“…Predominant ate complexation was also observed for Schumannsm ethyl complexes Li 3 LnMe 6 (thf) x [22] or diisopropylamido derivatives LiLn(NiPr 2 ) 4 (thf) x . [41] Crucially,i ndependent of the applied LuCl 3 (thf) x /n-BuLi stoichiometry,c omplex 3 Lu could be crystallized as the exclusive Lu III -containing species,u pon separation of the solution from unreacted rare-earth-metal halide,i ts evaporation to dryness,a nd extraction of the residue with n-hexane (XRD unit-cell check and 1 HNMR spectroscopy indicated repeatedly formation of 3 Lu ). This finding suggested that the typical reaction (preformation) conditions for alutetium-derived Imamoto reagent, LuCl 3 /n-BuLi/THF/À78 8 8C/30 min should form Li 3 Lu(n-Bu) 6 (thf) x as the dominant initial lutetium species in solution.…”
Section: Methodsmentioning
confidence: 99%
“…oder Diisopropylamid-Derivate LiLn-(NiPr 2 ) 4 (thf) x beobachtet. [41] Entscheidend ist auch, dass unabhängig von der verwendeten LuCl 3 (thf) x /n-BuLi-Stçchiometrie der Komplex 3 Lu als einzige Lu III -haltige Spezies kristallisiert werden konnte;u nd dies,n achdem die Lçsung von nicht umgesetztem Seltenerdmetallhalogenid abgetrennt, bis zur Tr ockene eingeengt und der Rückstand mit n-Hexan extrahiert worden war (Bestimmung der Elementarzelle (XRD) und 1 H-NMR-Spektroskopie zeigten wiederholt die Bildung von 3 Lu an). Dieser Befund deutet darauf hin, dass die typischen Reaktions-(Präformations-)Bedingungen füre in Lutetium-basiertes Imamoto-Reagenz, LuCl 3 /n-BuLi/THF/ À78 8 8C/30 min, Komplex Li 3 Lu(n-Bu) 6 (thf) x als die dominante anfängliche Lutetium-Spezies in Lçsung bilden sollten.…”
Section: Ergebnisse Und Diskussionenunclassified